Формування ідентичності: поляки, турки та євреї в українських думах - Гусейн Алюпінар (Народна творчість та етнографія, 2010)
To locate workings of identity in the duma texts, this paper will focus on the images of the «other». The working hypothesis is that these epics, by content, reflect the historical events of the era, that is the Cossacks' conflictive relations with the Poles, the Ottomans, the Tatars and the Jews, they would contain information about the definition of the «self» and the «other». Ukrayna halk destanlarında kimlik konusunu gözlemek amacıyla bu çalışma destanlarda bulunan «öteki» üzerine anlatımlara yoğunlaşacaktır. Burada dayanılan hipotez bu destanların içerik olarak Kozakların Lehlerle, Osmanlılarla ve Yahudilerle olan çatışmalarını anlatması nedeniyle «kendi» ve «öteki» üzerine bilgi içermesi gerektiğidir.